The impact of carbon information disclosure on corporate green technology innovation in the context of “dual carbon”—— Based on data from heavily polluting industries - Lumenqiqige Chao; Richa Hu; Boya Shi; Xiaomin Jin (PLoS ONE, 2025)
In the current global response to climate change, the “dual carbon” goal has become a common development goal for all countries. In the context of “dual carbon”, China’s heavily polluting enterprises, as the main governance body, have become the necessary path for green transformation. Green technology innovation is important for heavily polluting industries to achieve green transformation. Starting from the perspective of environmental regulation based on information disclosure, this article mainly explores the mechanism of carbon information disclosure promoting green technology innovation in enterprises. This article takes heavily polluting enterprises in China from 2017 to 2021 as samples and innovatively constructs a carbon information disclosure indicator system based on the “dual carbon” background. Then, empirical tests examine the relationship between carbon information disclosure level, green technology innovation, and financing constraints. Research has shown that the quality of carbon information disclosure improves corporate green technology innovation; The quality of carbon information disclosure can promote green technology innovation by alleviating corporate financing constraints. The research results have theoretical value and significance for incentivizing heavily polluting enterprises to reduce carbon emissions and support China’s dual carbon goals.